2021
DOI: 10.1007/s10875-020-00949-6
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profiles Before and After Immune Modulation in Hospitalized Patients with COVID-19

Abstract: We describe the cytokine profiles of a large cohort of hospitalized patients with moderate to critical COVID-19, focusing on IL-6, sIL2R, and IL-10 levels before and after receiving immune modulating therapies, namely, tocilizumab and glucocorticoids. We also discuss the possible roles of sIL2R and IL-10 as markers of ongoing immune dysregulation after IL-6 inhibition. We performed a retrospective chart review of adult patients admitted to a tertiary care center with moderate to critical SARS-CoV-2 infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
(29 reference statements)
3
14
0
1
Order By: Relevance
“…By day 10 post-symptom onset, 44 of 45 evaluable patients had detectable anti-Spike and anti-RBD total Ig (Figure 1b). IgG titers to Spike and RBD persisted through the acute phase of infection (day [10][11][12][13][14][15][16][17][18][19], recovery (day , and into late recovery (day 60 -120), whereas IgM titers started to decline in the recovery phase, as expected (Figure 1c). There was a corresponding increase in the frequency of antibody-producing plasmablasts, class switched IgD neg B cells, and T follicular helper cells (Tfh) by day 9 (Fig 1d).…”
Section: Robust Adaptive Immune Responses In Infected Patientssupporting
confidence: 70%
“…By day 10 post-symptom onset, 44 of 45 evaluable patients had detectable anti-Spike and anti-RBD total Ig (Figure 1b). IgG titers to Spike and RBD persisted through the acute phase of infection (day [10][11][12][13][14][15][16][17][18][19], recovery (day , and into late recovery (day 60 -120), whereas IgM titers started to decline in the recovery phase, as expected (Figure 1c). There was a corresponding increase in the frequency of antibody-producing plasmablasts, class switched IgD neg B cells, and T follicular helper cells (Tfh) by day 9 (Fig 1d).…”
Section: Robust Adaptive Immune Responses In Infected Patientssupporting
confidence: 70%
“…in our patient have provided evidence of cytokine storming and T-cell activation in the pathogenesis of COVID-19 related encephalopathy and CLOCCs. Indeed, several studies have shown a positive association of IL-6 and sIL2R levels with the disease severity, at least in adult patients with COVID-19 [14,15]. Notably, our patient recovered well following the immunomodulatory therapy, not requiring cytokine antagonists such as Tocilizumab.…”
Section: Discussionsupporting
confidence: 53%
“…Although the mechanisms leading to inflammation in COVID-19 are still poorly understood, immunomodulatory agents have rapidly been proposed and included into various clinical trials, most of them focused on IL-1b, -6, -8, and TNF-a (6,9,14). Azmy et al suggested that TCZ was unable to calm the inflammatory storm focusing on increased IL-10 and IL-2 receptor levels in patients receiving TCZ (2). However, the profile of a large panel of cytokines immediately after TCZ administration is yet unknown.…”
Section: Discussionmentioning
confidence: 99%